Integrative Framing Analysis Framing Health through Words and Visuals - Dan, Viorela (Routledge Research in Communication Studies, 2018)
Much of framing scholarship focuses either exclusively on the analysis of words or of visuals. This book aims to address this gap by proposing a six-step approach to the analysis of verbal frames, visual frames and the interplay between them-an integrative framing analysis. This approach is then demonstrated through a study investigating the way words and visuals are used to frame people living with HIV/AIDS in various communication contexts: the news, public service announcements and special interest publications. This application of integrative framing analysis reveals differences between verbal frames and visual frames in the same messages, underscoring the importance of looking at these frames together.